2020
DOI: 10.1002/adfm.202004307
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Drug‐Releasing Microporous Annealed Particle Scaffolds for Treating Myocardial Infarction

Abstract: Intramyocardial injection of hydrogels offers great potential for treating myocardial infarction (MI) in a minimally invasive manner. However, traditional bulk hydrogels generally lack microporous structures to support rapid tissue ingrowth and biochemical signals to prevent fibrotic remodeling toward heart failure. To address such challenges, a novel drugreleasing microporous annealed particle (drugMAP) system is developed by encapsulating hydrophobic drug-loaded nanoparticles into microgel building blocks vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 69 publications
0
77
0
Order By: Relevance
“…The adhesion between adjacent particles can be further improved if they are covalently crosslinked either upon direct contact, [121] light exposure, [70,71] or through enzymatically activated reactions, [68] as exemplified in figure 3 e . The covalent inter-particle crosslinking increases Young's modulus of the granular materials by a factor of 1.5 [70].…”
Section: Mechanically Stable Granular Materialsmentioning
confidence: 99%
“…The adhesion between adjacent particles can be further improved if they are covalently crosslinked either upon direct contact, [121] light exposure, [70,71] or through enzymatically activated reactions, [68] as exemplified in figure 3 e . The covalent inter-particle crosslinking increases Young's modulus of the granular materials by a factor of 1.5 [70].…”
Section: Mechanically Stable Granular Materialsmentioning
confidence: 99%
“…[12,13] Thus, granular hydrogels are ideally suited to promote the invasion of cells and blood vessels when used as injectable scaffolds for tissue repair. These desirable characteristics have motivated the development and application of granular hydrogels towards various biomedical applications including drug delivery, [14,15] immune modulation, [13,16] modular fabrication of biomaterials including with 3D printing, [1719] and as cell-instructive scaffolds. [2022]…”
Section: Main Textmentioning
confidence: 99%
“…In contrast to traditionally used non-porous bulk hydrogels, highly porous granular hydrogels support the invasion of cells and blood vessels within their volume, thereby fostering the requisite biological activity to promote endogenous tissue repair. [4,14,21] While several previous studies have investigated the adhesion, spreading, and migration of single cells throughout granular hydrogels as a function of particle properties, it remains unknown how endothelial cell sprouting – a process that mimics angiogenesis – is influenced by granular hydrogel properties. [34,35] This investigation is challenging in vitro because cells preferentially adhere and proliferate on particle surfaces, which reduces their ability to form lumen-like sprouts.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these approaches was conceived to deliver Forskolin and Repsox, which have previously been used in a reprogramming cocktail [128,141], using microporous annealing particles incapsulated into hydrogel blocks to drive tissue growth and local compound release. Although not aimed at cardiac reprogramming, these experiments showed that chemical reprogramming compounds could be released in a time and space dependent manner, retaining their ability to functionally modulate the activity of CMs, CFs, and ECs both in vitro and in vivo settings [165]. The second experience reports a nanoparticle based simultaneous delivery of CHIR99021 and Fibroblast Growth Factor 1 (FGF1).…”
Section: Nanotechnology-based Approaches For Direct Cardiac Reprogrammingmentioning
confidence: 99%